100: IMPACT OF INCREASING LYMPH NODE YIELD ON THE NUMBER OF POSITIVE LYMPH NODES, MORBIDITY AND SURVIVAL IN ESOPHAGEAL CANCER SURGERY. (23rd April 2022) - Henckens, S; Hagens, E; Eshuis, W; Meijer, S; Van Berge Henegouwen, M; Gisbertz, S
Abstract: Background and aim: Accurate determination of lymph node status after esophagectomy requires complete lymphadenectomy. Extended surgery might also lead to more postoperative morbidity. This study analyzed lymph node yield over time and investigated the influence of lymph node yield on the number of positive lymph nodes, postoperative morbidity and disease-free survival. Methods: Patients who underwent transthoracic esophagectomy for esophageal adenocarcinoma between 2010 and 2018, were included. Lymph node yield was both analyzed as continuous variable and as categorical variable (<15, 15–29 (reference category) and ≥ 30 nodes). The effect of lymph node yield on the number of positive lymph nodes, morbidity and disease-free survival was assessed in multivariable regression analyses. Results: A total of 469 patients were included with a median follow-up of 20 months. The majority of the included patients received neoadjuvant chemo(radio)therapy (93.1%). The median lymph node yield increased from 25.0 lymph nodes (IQR 20–34) in 2010 to 36.0 lymph nodes (IQR 30–45) in 2018. Higher lymph node yield was significantly associated with more positive lymph nodes both as continuous variable (IRR 1.020, 95%CI 1.006–1.034), and as categorical variable with a threshold of ≥30 nodes (IRR 1.549, 95%CI 1.069–2.244). Lymph node yield was not associated with morbidity. Lymph node yield was not associated with disease-free survival when analyzed as a continuous variable (HR 0.996, 95%CI 0.984–1.008). There was also no difference in disease-free survival between patients with a lymph node yield of <15 and 15–29 (reference) (HR 1.362, 95%CI 0.793–2.338), and between patients with a lymph node yield of 15–29 (reference) and ≥ 30 (HR 0.849, 95%CI 0.650–1.109). Conclusion: A higher lymph node yield after esophagectomy was associated with a higher number of positive lymph nodes; a higher number of resected lymph nodes therefore improves staging. A higher lymph node yield did not result in increased morbidity and no association between lymph node yield and disease-free survival could be demonstrated in patients undergoing esophagectomy after neoadjuvant chemo(radio)therapy.